THE EFFECT OF KICK SPEED, AGILITY, AND CONFIDENCE ON THE ACHIEVEMENT OF YOUNG PENCAK SILAT ATHLETES IN WEST SUMATRA - Wulandari, Suci; Widiastuti; Widyaningsih, Heni (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This study focuses on the relationship between attack speed, agility, and athlete achievement in pencak silat sports. This research also explores the role of self-confidence as a mediator in the relationship. The purpose of this study is to identify the direct and indirect influence of attack speed and agility on the achievement of pencak silat athletes by taking into account the role of confidence as a mediating variable. This research method uses the statistical analysis path method to test the relationship between these variables. Data were collected from pencak silat athletes and analyzed using significance tests to determine direct and indirect influences. The results of the study showed: attack speed had a direct significant influence on confidence (significance value 0.025 < 0.05), Agility had a direct significant influence on confidence (significance value 0.043 < 0.05), Attack speed had a direct significant influence on achievement (significance value 0.026 < 0.05), Agility had a direct significant influence on achievement (significance value 0.043 < 0.05), Confidence has direct significant influence on achievement (significance value 0.000 < 0.05), Attack speed has an indirect influence through confidence on achievement greater than its direct influence, Agility has an indirect influence through confidence on achievement greater than its direct influence. The conclusion of this study shows that attack speed and agility have a significant influence on the achievement of pencak silat athletes, both directly and through confident mediation. The development of attack speed, agility, and confidence should be the main focus in the training program to improve the athlete's performance